The Influence of Organizational Culture, Incentives and Work Motivation on Job Satisfaction in the Regional Government at Mebidangro Region - Haikal Rahman; Agus Rahmadsyah; Khafi Puddin (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
The important thing in human resource management is to manage the human element properly in order to obtain a workforce who is satisfied with their work. Employee job satisfaction is a factor that can affect the organization as a whole. Job satisfaction factors provide good benefits for the organization. Therefore, there are several ways that organizations can do to maintain and maintain their human resources, namely by providing motivation, presenting a conducive organizational culture, providing appropriate incentives to employees and others. other. This study aims to analyze the direct influence of organizational culture and incentives on employee work motivation at the Mebidangro Regional Government, to analyze the direct influence of organizational culture, incentives and work motivation on employee job satisfaction at the Mebidangro Regency Government. Mebidangro area. , and to analyze the indirect effect of organizational culture and compensation on job satisfaction through employee motivation at the Mebidangro Regional Government. The method used is the quantitative causality method. The population in this study were 37 respondents. The results of the study indicate that organizational culture and incentives have a direct effect on the work motivation of employees of the Regional Government of the Mebidangro Region and have a positive and significant effect on employee job satisfaction. Then the organizational climate and compensation indirectly have a positive but not significant effect on job satisfaction through the work motivation of employees at the Regional Government of the Mebidangro Region.